On positive solutions for a class of elliptic systems involving the p(x)-laplacian with multiple parameters - Afrouzi, Ghasem Alizadeh (2014)
In this article, we consider the system of differential equations (equations presented) where Ω ⊃ RN is a bounded domain with C2 boundary δΩ, 1< p(x)εC1 (Ω̄) is a function. The operator (equations presented) is called p(x) -Laplacian, λ,λ1,λ2,μ1 and μ2 are positive parameters. We prove the existence of positive solutions when (equations presented) via sub-supersolutions without assuming sign conditions on f (0), g(0), h(0) or τ (0) .